Retorik al-Mujadalah dalam dakwah: Kajian terhadap kisah Nabi Ibrahim a.s. didalam al-Quran / Rohaily @ Abd Rahman Abd Hamid - Rohaily , Abd Rahman @ Abd Hamid (2018)
Al-Mujādalah is one of the messengers' preaching methods. It means debating, discussing or exchanging arguments and opinions. The reality now indicates that many Muslims generally do not understand the demands of arguing well, and in fact some preachers also fail to handle certain situations properly, at times being too emotional and merely thinking of trying to kill off his opponent’s argument to win the mujādalah. It seems pursuing the mujādalah with good and effective rhetoric has become an increasingly forgotten requirement of today's preachers. As a result, a perfect and beautiful Islam looks bad and ugly to the world. As a community that promotes Islam, the daie should ensure that whatever they present in the name of Islam corresponds to religious values, so that Islam can be seen in its truest beautiful form for all to witness. This study entitled 'The Rhetoric of Al-Mujādalah In Da'wah: Study of the Tale of Prophet Ibrahim a.s. in the al-Qur'an' is a documentary study of Prophet Ibrahim a.s. which presents his mujādalah rhetoric covering all levels of society, as laid out in the al-Quran. The study is undertaken to realise three main objectives: first, to study the concept of al-mujādalah in preaching activities through the Quranic perspective, second, to identify the preaching methods and al-mujādalah approaches employed by Prophet Ibrahim a.s. when he preached, as stated in the al-Quran, and third, to analyse the al-mujādalah rhetoric employed by Prophet Ibrahim a.s. based on verses of the al-Quran. The study was undertaken using data gathered through library searches and qualitative data analysis as the main methods of study, besides using inductive and deductive methods as support. The resulting information are based on the Al-Quran, and references to 33 venerated books on tafsir containing various statements on the al-mujādalah rhetorics of Prophet Ibrahim a.s. The main outcome of the study is the presentation of a guide to having debates and dialogues with effective rhetoric based on the al-Quran. It is suitable as a reference for all parties who are involved in al-mujādalah, and also as a reference for institutions of higher learning, organisations, NGOs and preachers in general. May the result of this study be of benefit to all parties and help to preserve the beauty of our religion, the harmony of our life and the well-being of Muslims in particular, and of the whole human race in general.